Avaliação da reatividade de anticorpos anti-Toxoplasma gondii pela técnica de citometria de fluxo como indicadores de lesão ocular em soros de recém-nascidos com toxoplasmose congênita - Jesus, Laura Néspoli Nassar Pansini de (2014)
Retinochoroiditis is the most important disorder caused by Toxoplasma gondii infection. Because of severity of ocular lesions that can lead to blindness, early detection of congenital toxoplasmosis and ocular lesion are critical to treatment. The purpose of this study was evaluate the research applicability of IgG and subclasses IgG1, IgG2, IgG3 and IgG4 by flow citometry as a laboratorial biomarker for different forms of ocular lesions in congenital toxoplasmosis. For this purpose, was investigated the presence of antibodies anti-T. gondii IgG and subclasses by flow citometry. 88 serum samples from newborns with congenital toxoplasmosis were analyzed, of these, were 25 without ocular lesions (SL), 10 with active ocular disease (RA), 26 with active and cicatricial ocular lesions (RAC) and 27 with cicatricial ocular lesions (RC). Were also used 19 serum samples from uninfected infants with a positive IgG after birth (NI). These samples were obtained from Neonatal Screening Program in Minas Gerais, Brazil performed in the years 2006 and 2007. The results demonstrate that infants with congenital toxoplasmosis showed greater reactivity of antibodies IgG and subclasses IgG1, IgG2 and IgG3 than newborns uninfected. In the non-infected group the only antibody with over 50% of individuals with high antibody reactivity was IgG4. Among infants infected, the group of patients with lesions RAC showed greater reactivity to IgG and subclasses IgG1, IgG2 and IgG3 than infants groups of RC, RA and SL. Patients in group RA showed greater reactivity to IgG4 than other groups. IgG1 was the only subclass capable to differentiate group NI and SL than group RAC and RC. Was also evaluated IgG avidity that not allowed to establish any criteria for differentiating forms of eye lesion caused by Toxoplasma. Therefore, the results demonstrated that flow citometry can be used as an additional biomarker for different forms of retinochoroiditis.